2019
DOI: 10.1080/19490976.2018.1560768
|View full text |Cite
|
Sign up to set email alerts
|

The impact ofin uteroHIV exposure on gut microbiota, inflammation, and microbial translocation

Abstract: HIV-exposed but uninfected (HEU) children represent a growing population and show a significantly higher number of infectious diseases, several immune alterations, compromised growth, and increased mortality rates when compared to HIV-unexposed children. Considering the impact that the gut microbiota has on general host homeostasis and immune system development and modulation, we hypothesized that HEU children present altered gut microbiota that is linked to the increased morbidity and the immune system disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 67 publications
6
30
0
Order By: Relevance
“…Furthermore, O 2 − indirectly kills microorganisms via proteolytic digestion of microorganisms. Indeed, O 2 − leads to depolarization of the phagosome membrane and a compensating influx of H + and K + into the phagolysosome, which removes proteases from the anionic proteoglycan matrix by raising ionic strength [ 44 , 45 ].…”
Section: Roles Of Reactive Oxygen Species In the Immune Systemmentioning
confidence: 99%
“…Furthermore, O 2 − indirectly kills microorganisms via proteolytic digestion of microorganisms. Indeed, O 2 − leads to depolarization of the phagosome membrane and a compensating influx of H + and K + into the phagolysosome, which removes proteases from the anionic proteoglycan matrix by raising ionic strength [ 44 , 45 ].…”
Section: Roles Of Reactive Oxygen Species In the Immune Systemmentioning
confidence: 99%
“…HIV infected children present reduced gastrointestinal microbial diversity [154]. Modulation of the intestinal microbiome through nutritional supplementation, with the aim of decreasing bacterial permeability, has been attempted in the context of HIV infection with scarce success [155,156].…”
Section: Microbiome and Infection In Infantsmentioning
confidence: 99%
“…Nowadays, a lot of research is performed on the influence of the gut microbiota on infant development and metabolism, a lot of which involves maternal Ig derived from mother's milk or retro-transported via the FcRn receptor from the serum to the gut (34). Gut microbiota develops via interactions with nutrients (35), both endogenous and exogenous agents, such as melatonin (36) or fructans (37), and even viral infections (38), with involvement of maternal and infant Ig. Recently (39), it has been shown that maternal IgA decreases the risk of development of necrotizing enterocolitis through its (IgA) influence on the host-microbiota relationship in preterm neonates.…”
Section: Maternal Ig Support Structural and Functional Development Ofmentioning
confidence: 99%